2017
DOI: 10.1038/srep43292
|View full text |Cite
|
Sign up to set email alerts
|

When to stop propranolol for infantile hemangioma

Abstract: There is no definitive conclusion regarding the optimal timing for terminating propranolol treatment for infantile hemangioma (IH). A total of 149 patients who underwent detailed color Doppler ultrasound examination were included in this study. The characteristics and propranolol treatment of all patients were summarized and analyzed. Patients were divided into two groups according to the lesion regression rate. Among the 149 patients, 38 were assigned to the complete regression group, and 111 were assigned to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 32 publications
1
47
0
3
Order By: Relevance
“…stopped propranolol treatment when there was no obvious blood flow signal on ultrasound, resulting in no IH regrowth. Chang et al . insisted that propranolol can be stopped when patients are older than 1 year of age and achieve maximal reduction for more than 3 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…stopped propranolol treatment when there was no obvious blood flow signal on ultrasound, resulting in no IH regrowth. Chang et al . insisted that propranolol can be stopped when patients are older than 1 year of age and achieve maximal reduction for more than 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…26 Shi et al 26 stopped propranolol treatment when there was no obvious blood flow signal on ultrasound, resulting in no IH regrowth. Chang et al 27 insisted that propranolol can be stopped when patients are older than 1 year of age and achieve maximal reduction for more than 3 months. To measure the surface temperature of IH by using an infrared thermometer helps to predict their proliferative potential.…”
Section: Discussionmentioning
confidence: 99%
“…The decision to stop propranolol treatment is difficult, but ultrasonography may be helpful . Chang et al .…”
Section: Discussionmentioning
confidence: 99%
“…The decision to stop propranolol treatment is difficult, but ultrasonography may be helpful. 4 Chang et al 4 insisted that propranolol can be stopped when patients are older than 1 year of age and achieve maximal reduction for more than 3 months. Using an infrared thermometer to measure the surface temperature of IH helps to predict their proliferative potential.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging studies have reported that propranolol could significantly inhibit the development of IH [12] Quantitative Real-Time PCR TRIzol reagent (Invitrogen, Carlsbad, CA, USA) was applied to extract total RNA according to the manufacturer's instructions. Using the High Capacity cDNA Reverse Transcription Kit (Applied Biosystems, Foster City, CA, USA), 1 μg RNA was reversetranscribed into cDNA To detect the mRNA levels of Caspase-3, B-cell lymphoma (Bcl-2) and Bcl-2-associated X protein (Bax), quantitative real-time-PCR was performed with SYBR Green master mix (Roche, Mannheim, Germany).…”
Section: Introductionmentioning
confidence: 99%